Uji Kualitatif Penurunan Kadar Lemak, Kandungan Padatan, dan Kekeruhan Pada Air Limbah Domestik Dengan Grease Trap Bar Screen Filtration - Rena Jayana; Khoerun Nisa; Saputri Anggraeni Pusphaningrum (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2021)
Sources of water pollution are usually derived from industrial or factories, homes, markets, rice fields, and hospital liquid waste. Water that contains detergent, feces and leftover foods that go into the drain daily can affect the balance of physics and chemistry of water. Residues that go into the sewer pipes can cause a blockage in the pipes. The objective of this study was to use a filtration bar screen grease trap to lower fat content, solids, and turbidity in domestic wastewater (dish-cleaning wastewater). The study is divided into two main stages which is the grease trap filtration bar screen assembly and the process for the grease trap. The grease trap works to catch leftover dirt and fats so that they do not block the pipes in the drain. Dish-cleaning sewage that has been processed in grease trap is not clogging up pipes in the sewer because the filtration process had separate solids and fats/oil. Fat content, solids, and turbidity is decreased after treatment. The modification of grease trap is possible so it does not only separate leftover food, fat or oil, but also purify wastewater by decreasing Total Suspended Solid (TSS).